Keadilan Bagi Anak Luar Kawin dalam Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010 - Farahi, Ahmad; Ramadhita, Ramadhita (Fakultas Syariah, 2016)
This article intents to examine the civil rights of children outside of married arising from Constitutional Court Decision No. 46 / PUU-VIII / 2010 review by justice aspects. This article is normative juridical research with a qualitative approach to the primary legal materials, namely Law No. 1 of 1974 on Marriage and the constitutional Court Decision No.46 / PUU-VIII / 2010. While the secondary legal materials such as books, journals, research related to children outside of married. Before the decision of the Constitutional Court No. 46/PUU-VIII/2010 was issued, children outside of marriage do not get the personal law rights, both the principles of Islamic justice and the West, as well as human rights perspective. After the emergence of Constitutional Court Decision No. 46 / PUU-VIII / 2010, children outside married have the same status as a legitimate child, with the requirement to have medical evidence.Artikel ini bertujuan mengkaji hak-hak keperdataan anak luar kawin yang muncul akibat Putusan Mahkamah Konstitusi No. 46/PUU-VIII/2010 ditinjau dari aspek keadilan. Artikel ini merupkan hasil penelitian yuridis normatif dengan pendekatan kualitatif dengan bahan hukum primer yaitu Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan dan Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010. Sedangkan bahan hukum sekunder berupa buku, jurnal, penelitian terkait anak luar kawin. Sebelum putusan Putusan Mahkamah Konstitusi No. 46/PUU-VIII/2010 dikeluarkan, anak luar kawin tidak mendapatkan hak-hak keperdataannya secara adil. Baik menurut prinsip keadilan Islam, Barat, maupun perspektif HAM. Pasca munculnya Putusan Mahkamah Konstitusi No. 46/PUU-VIII/2010, anak luar kawin memiliki kedudukan yang sama dengan anak sah, dengan syarat memiliki bukti medis.